Gerakan Literasi Masyarakat: Membangun Masyarakat Literat Melalui Penguatan Literasi - Diningrum Citraningsih (STAI Terpadu Yogyakarta, 2023)
Taman Pojok Literasi was established in Bulak Gempol Nguter Pasirian Lumajang in 2013. This effort to establish a literacy corner park is an excellent step to overcome the problem of low reading interest and literacy among children and society in general. In this study, PAR (Participatory Acion Research) was used. PAR research is a research approach that involves all relevant parties actively and participatively to assess the actions that take place. The purpose of this method is to improve action actions through the conduct of research and participation of researchers in action. In their article entitled Community Literacy Movement: Strengthening Lerasi to Build a Literate Society, the authors show how important literacy is for the general public and children.